Sosialisai Penetapan Harga Jual Produk Terhadap Profit UMKM di Kelurahan Karang Joang - Jepri Jepri; Karina Amilia; Franky Purnama Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Almost all and the majority of MSME owners in Karang Joang Village, Balikpapan City, precisely in Gang Banyumas KM 15 RT 32 and its surroundings, have an inadequate understanding of the proper calculation of product selling prices. MSME owners have not identified and calculated costs optimally, causing the profit generated to be less than optimal. In response to this problem, the researcher will implement the work program